2009
DOI: 10.1158/1078-0432.ccr-08-3150
|View full text |Cite
|
Sign up to set email alerts
|

Proposal and Validation of Prognostic Scoring Systems for IgG and IgA Monoclonal Gammopathies of Undetermined Significance

Abstract: Purpose:The presenting clinico-hematologic features of 1,283 patients with IgG and IgA monoclonal gammopathies of undetermined significance (MGUS) were correlated with the frequency of evolution into multiple myeloma (MM). Experimental Design: Two IgG MGUS populations were evaluated: a training sample (553 patients) and a test sample (378 patients); the IgA MGUS population consisted of 352 patients. Results: Forty-seven of the 553 training group patients and 22 of 378 test group IgG patients developed MM after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…From this finding, we believe that IgA myeloma patients might have stronger immunological suppression than IgG myeloma patients which could also influence survival. To support this hypothesis, several clinical data reported that IgG myeloma patients had better prognosis than IgA myeloma patients but difference between IgG and IgA myeloma patients with regard to immune status/performance and functions are yet to be revealed [42], [43]. There are reports available showing that stage dependent increases of Treg cells in MM and B-CLL and our data also corroborate this finding but lacks statistical significance [23], [44].…”
Section: Discussionsupporting
confidence: 78%
“…From this finding, we believe that IgA myeloma patients might have stronger immunological suppression than IgG myeloma patients which could also influence survival. To support this hypothesis, several clinical data reported that IgG myeloma patients had better prognosis than IgA myeloma patients but difference between IgG and IgA myeloma patients with regard to immune status/performance and functions are yet to be revealed [42], [43]. There are reports available showing that stage dependent increases of Treg cells in MM and B-CLL and our data also corroborate this finding but lacks statistical significance [23], [44].…”
Section: Discussionsupporting
confidence: 78%
“…Clonal burden as determined by BM plasma cell percentage 10,12-16 and/or M-protein size 4,10,[12][13][14][15][17][18][19][20][21][22][23] is an important risk factor for malignant transformation of MGUS. Furthermore, Rosinol et al showed that a progressive increase of the M-protein (evolving MGUS) is predictive of progression.…”
Section: Predictors Of Malignant Transformation In Mgusmentioning
confidence: 99%
“…Tumor load • M-protein level 4,10,[12][13][14][15][17][18][19][20][21][22][23]31 • [40][41][42]44 but not in others. [37][38][39]43 Also after allogeneic (allo)-SCT development of secondary MGUS has been described.…”
Section: Predicting Factors Of Progression At Baseline Time-dependentmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with consistently reduced serum Ig concentrations are more susceptible to infections [4][5][6][7][8], and may be associated with an increased risk of developing cancer, particularly hematological neoplasms, as observed in patients with common variable immunodeficiency [9][10][11]. Moreover, 8-35% patients with monoclonal gammopathy of unknown significance (MGUS) have been reported to have reduced polyclonal (uninvolved, nonparaprotein) Ig [12][13][14], and this reduction in uninvolved Ig is associated with an increased risk of malignant transformation [14][15][16]. Somewhat higher incidences of hypo-Ig have also been reported in other lymphoproliferative diseases such as chronic lymphocytic leukemia (up to 85% at some stages) [18], Waldenstrom's macroglobulinemia (63% and 58% with IgA and IgG reductions respectively) [19] and smoldering multiple myeloma (45-83%) [20][21][22].…”
Section: Introductionmentioning
confidence: 99%